Causes and prevention of sports injuries in youth basketball - Kong, D. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Basketball is a fast, intense sport requiring much reasoning and dexterity. It comprises running, jumping, throwing, and other injuries. Students and sports fans deeply love this sport. However, due to the characteristics of basketball, there are many risks of sports injuries in basketball. Objective: Investigate the causes of sports injuries in youth basketball training and evaluate preventive countermeasures. Methods: This paper analyzes basketball's injury mechanism, causes, and occurrence rules through survey questionnaires. Statistical analysis and recent literature research are performed to support a preventive protocol. Results: A protocol for injury prevention and mitigation in basketball was presented. Conclusion: To ensure normal training and competition in basketball, one must pay attention to the intrinsic characteristics of injuries in its players, considering the multiple variables that integrate the risks to the athletes' health.